1999
DOI: 10.1046/j.1442-2042.1999.06446.x
|View full text |Cite
|
Sign up to set email alerts
|

Metanephric adenoma of the kidney

Abstract: Background: Metanephric adenoma is a rare renal neoplasm that is histologically and clinically unique. We found this neoplasm in a 62-year-old female, whose renal tumor was incidentally detected on abdominal ultrasound examination. Methods/Results: Ultrasound, computed tomography and magnetic resonance imaging were compatible with those of renal cell carcinoma. With a diagnosis of renal cell carcinoma, right partial nephrectomy was performed. This tumor showed histologic similarity to developing metanephric tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…Although most of the MA reported previously were non-encapsulated, 4,9,17,21,[25][26][27]29,35,41 a thin, distinct and mainly discontinuous fibrous pseudocapsule has been described in at least 30 cases. 4,20,23,24,30,32,34,40,42 Conversely, 87% of s-PRCC included in this study were surrounded by a thick fibrous pseudocapsule, and fibrosis was noted at the tumour/normal interface in the three remaining cases. This finding is consistent with one series of five s-PRCC 8 and one case report, 37 where the tumours showed a dense fibrous pseudocapsule.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although most of the MA reported previously were non-encapsulated, 4,9,17,21,[25][26][27]29,35,41 a thin, distinct and mainly discontinuous fibrous pseudocapsule has been described in at least 30 cases. 4,20,23,24,30,32,34,40,42 Conversely, 87% of s-PRCC included in this study were surrounded by a thick fibrous pseudocapsule, and fibrosis was noted at the tumour/normal interface in the three remaining cases. This finding is consistent with one series of five s-PRCC 8 and one case report, 37 where the tumours showed a dense fibrous pseudocapsule.…”
Section: Discussionmentioning
confidence: 77%
“…45 Other studies have described negative staining for S100 in MA. 9,20,34,35,41 No previous studies have analysed the immunoreactivity of s-PRCC for S100 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these tumors had been diagnosed previously as nephroblastoma or renal cell carcinoma (4) or have been published under different diagnoses but fitted in the histological image of Mostofi and Brisigotti [5]. Since 1995, 39 cases of tumors with the typical morphology have been reported under the term of metanephric adenoma [3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we perform transperitoneal radical nephrectomy as the gold standard for the management. In other cases, Kosugi et al, Imamoto et al, Granter et al reported performing partial nephrectomy [23,24,25].…”
Section: Discussionmentioning
confidence: 99%